THE INFLUENCE OF ETHNOMATHEMATICS BASED LEARNING ON MATHEMATICS PROBLEM-SOLVING ABILITY: A META-ANALYSIS - Apriatni, Sri; Syamsuri, Syamsuri; Nindiasari, Hepsi; Sukirwan, Sukirwan (Jurnal Pendidikan Matematika (JUPITEK), 2022)
The introducer of ethnomathematics defined ethnomathematics as mathematics practised among identified cultural groups. Ethnomathematics positively impacts the learning process either as a Moderate or an approach to, for example, problem-solving ability. Previous researchers have carried out several studies on implementing ethnomathematical-based learning to improve students’ problem-solving ability. However, the analysis shown is very varied, so it still raises doubts about the impact of learning using ethnomathematics on mathematical problem-solving abilities. This study aims to determine the correlation between ethnomathematical-based with students’ problem-solving skills. This study uses meta-analysis research, which combines several experimental Studies that collate the effectuality of ethnomathematical-based learning and regular instruction on improving the mathematical problem-solving ability. Relevant studies were searched through e-resources from Perpusnas databases with the specified keywords. There are 106 studies obtained from the search query. Fourteen studies were selected according to the inclusion and exclusion criteria. Meta-Mar was used to determine the joined effect size by analysing the selected studies. This study shows that the joined effect size of applied ethnomathematical-based learning in improving mathematical problem-solving skills is 1,04 and was classified as a strong effect. Therefore, it is deduced that ethnomathematical-based learning relies on mathematical problem-solving abilities. Statistically, the implementation of ethnomathematics-based learning in improving mathematical problem-solving ability is also influenced by the study’s characteristics at the level of education.